Development of Hygyene and Sanitation Learning Tools Based on Typical Food “Mbohi Dungga” Using PBL Model to Improve Students' Creative Thinking Ability - Mahfud, Mahfud; Feriyadin, Feriyadin (Jurnal EduHealth, 2022)
Research on hygiene and sanitation courses has been carried out on students of the tourism study program at STIPAR Soromandi Bima. This study aims to develop a hygiene and sanitation learning tool based on typical food "Mbohi Dungga" using the PBL model to improve students' creative thinking skills. By using a 4-D model (developmental research) which include of RPS Textbooks, Worksheets and Instruments of students' creative thinking skills. Based on the objectives and results of the study, it can be concluded that the procedure for developing hgyene and sanitation learning devices based on typical food "Mbohi Dungga" using Problem Based Learning Models to improve creative thinking ability of STIPAR Soromandi Bima students by using the Four-D research development model is in the "GOOD" category. Thus, the learning tools developed can be declared "FEASIBLE" to be used in the learning process in the Hygyene and Sanitation course at STIPAR Soromandi Bima.